Incidence and survival of soft tissue sarcoma in England between 2013 and 2017, an analysis from the National Cancer Registration and Analysis Service. Issue 9 (11th January 2023) - Bacon, Andrew; Wong, Kwok; Fernando, Malee S.; Rous, Brian; Hill, Roger J. W.; Collins, Shane D.; Broggio, John; Strauss, Sandra J.
Abstract: There is a paucity of population‐based data detailing the incidence and survival of patients with soft tissue sarcoma (STS), in part due to the heterogeneity of disease and changes to classification. Here, the incidence and survival of all STS subtypes registered in England between 2013 and 2017 were analysed using cancer registry data held by the National Cancer Registration and Analysis Service. Age‐standardised incidence rates were calculated per 1 000 000 using the 2013 European Standard Population. Net survival was computed using Brenner's alternative method, with the Ederer II estimator. Age‐specific overall survival was assessed using Kaplan‐Meier. The influence of age, sex, socioeconomic deprivation and diagnostic routes on survival was assessed using Cox proportional hazards modelling. In total, 19 717 patients were diagnosed with STS, an average of 3943 patients per year and representing approximately 0.8% of malignancies. The most common histological diagnoses were Gastrointestinal Stromal Tumours (GIST), leiomyosarcoma and undifferentiated sarcoma, accounting for 20.2%, 13.3% and 12.7% of all sarcomas, respectively. Five‐year net survival for all malignant STS was 65.0%; and was lowest for patients with vascular tumours at 39%. Patients from most deprived cohorts had 23% greater chance of dying within 5 years than patients in least deprived areas. This population‐based study has allowed us for the first time to define the incidence and survival rates of prevalent STS subtypes in England such as GIST, liposarcoma and leiomyosarcoma, as well as rare entities and groups with inferior outcome. This data is invaluable for service provision, benchmarking and addressing inequality. Abstract : What's new? Histological and anatomical diversity of soft tissue sarcoma (STS), along with variability in classification and reporting, present major challenges for understanding STS incidence and survival. In our study, STS incidence and outcome were analysed for an English population using the 2013 World Health Organisation classification system for soft tissue tumours and data from England's National Cancer Registration and Analysis Service. Analyses show that, on average, more than 3900 patients were diagnosed with STS in England annually from 2013 to 2017, with an overall incidence of 78 persons per million. Overall, 65% of patients with malignant STS survived 5 years with outcome varying across age groups.